Zrób mi jakąś krzywdę… by Jakub Żulczyk as a Contemporary “Diary from the Period of Adolescence” - Kurkiewicz, Marek (Porównania, 2023)
The article presents an analysis of puberty, one of the key aspects of Jakub Żulczyk’s debut novel Zrób mi jakąś krzywdę… (2006). At the same time, he presents potential analogies with the interwar volume of Witold Gombrowicz’s Pamiętnik z okresu dojrzewania (1933), whose characters try in various ways to “grow up” to the surrounding Forms. In Żulczyk’s writings, there is something immature in almost every created character, regardless of the age or experience. The best example of this is a pair of main characters: the twenty-five-year-old David and his kidnapped teenager, a brilliant, alienated girl, locked in the world of video games. During the initiation journey, under the influence of various factors, each of them undergoes a metamorphosis, maturing, slowly crossing the boundaries of childhood. Żulczyk collides various contemporary types of immaturity, at the same time provoking the question about the condition of adulthood in today’s world.